Padrões de ocorrência e composição de girinos do cerrado: importância da interação fenótipo-ambiente e do espaço - Marques, Núbia Carla Santos (2016)
Tadpoles of anuran species that occur in Cerrado can be found in several types of habitats. This habitat plasticity is possible because tadpoles have a high diversification in morphological adaptations that ensure an optimal performance in different ecological contexts. In this study, we were interested to investigate how environmental and spatial factors can explain the patterns of occurrence and distribution of tadpoles in Brazilian Cerrado and the interaction with tadpoles‘ morphological variation. We found that occurrence of tadpoles was explained by environmental variables and seven morphology-environment interactions. The most common tadpoles morphological change is related to body and tail size, and in eyes, nostril and mouth positions. Tadpoles‘ assemblage composition and morphological variation have significantly affected by spatial factors, but local environmental factors also play a major role defining morphological variation, although to a small degree. We discuss ecomorphological guilds of tadpoles and suggest that in larger guild (benthic tadpoles) can have morphology-environment interaction, while in the smaller ones (nektonic tadpoles) changes in feeding behavior and habitat selection is more common. There is a lack of knowledge about amphibian diversity, abundance and occurrence in Brazilian Cerrado and our study provide additional information about environmental and spatial factors that contribute to the patterns of occurrence and distribution of species. Abiotic factors (e.g. vegetation in ponds and land use) and spatial factors can contribute to individuals‘ phenotype changes and play a role in patterns of occurrence and tadpoles‘ assemblage composition.